Development of Linguistic Competence in English for Specific Purposes Through ChatGPT: A Case Study - Miguel Ángel Jordán Enamorado (Journal of Language and Education)
Introduction: The launch of ChatGPT has popularized the use of Artificial Intelligence and has opened a debate about the opportunities and risks of this digital tool. Although it is still in development, ChatGPT offers numerous application possibilities as an educational resource.